Baclofen Withdrawal-Induced Psychosis in the Setting of Renal Insufficiency - Guilmette Amanda; Palushi Ambra; Shamsan Hundaol MD; Bhattacharyya Aniruddha MD; Michael Miriam MD (SAGE Publishing, 2022)
Baclofen is used to treat muscle spasticity, acting at GABA B receptors in the central nervous system. The abrupt cessation of baclofen causes baclofen withdrawal-induced psychosis. The risk is exacerbated if the patient has renal insufficiency or if the drug has been taken for a long time at high doses. Gradual tapering of baclofen usually does not produce symptomatic adverse effects. However, abrupt termination of the drug, especially in an inpatient hospital setting, can lead to symptoms such as increased spasticity, agitation, confusion, hallucinations, and seizures. We present a case of a patient who initially presented with seizures and experienced hallucinations after abrupt cessation of the medication. She had baseline chronic kidney disease but presented with acute worsening of her renal function. Impaired renal function decreases baclofen clearance and causes increased concentration of baclofen in circulation. This put the patient at higher risk of developing baclofen withdrawal, even at a lower dose.